Pengaruh Celebrity Endorser Fadil Jaidi terhadap Kesadaran Merek Traffic Bun - Nugraha, Muhamad Dhio; Dirgantara, Pradipta (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
This study was conducted to determine how much influence Celebrity endorser Fadil Jaidi has on Traffic Bun Brand Awareness. The population used in this study is Fadil Jaidi's Instagram followers, and uses quantitative methods with 400 respondents who participated in filling out questionnaires through online media selected through probability sampling. The analysis techniques used are simple linear analysis and descriptive analysis. The results of this study first show that the relationship between celebrity endorsers and brand awareness has a positive effect. Second, Fadil Jaidi, as a celebrity endorser, has a 45.8% effect on brand awareness of Traffic Bun products. Meanwhile, 54.2% of the other influence is influenced by other factors that were not examined by the researcher.